Aquacrop and ensemble global climate models for rice production under climate change impact - Ali, Houma Abdusslam Ahmad (2021)
Lowland paddy rice in Northwest Selangor, particularly in Tanjong Karang Rice Irrigation Scheme (TAKRIS), is the main crop grown during July to October (wet/main season) and January to April (dry/off-season). Climate change is one of the main environmental problems of the current century that directly affects growing conditions of most crops, including rice. This study evaluated the impacts of climate change on rice production in an area within TAKRIS. FAO-AquaCrop model was applied under 18 General Circulation Models (GCMs) with three levels of climate sensitivity (RCP4.5, RCP6.0 and RCP8.5) to assess yield potential of rice. Future projections of multi-GCMs in the study region have shown that temperature will increase under all emission scenarios, with the largest changes during the dry season. Compared to the baseline period (1976 to 2005), the projected increase in maximum temperature ranges from 0.6 to 1.5°C during the 2020s, 0.5 to 1.7°C during the 2050s and 0.7 to 3.01°C during the 2080s period and that in minimum temperature ranges from 0.7 to 1.7°C during the 2020s, 0.6 to 1.8°C during the 2050s and 0.8 to 3.2°C during the 2080s under RCP4.5, RCP6.0 and RCP8.5 scenarios, respectively. Rainfall projections show average changes of –0.3% during the 2020s, –0.22% during 2050s and –3.25% during the 2080s for the dry season, and 7.6% during 2020s, 6.8% during 2050s and 11% during the 2080s for the wet season under RCP4.5, RCP6.0 and RCP8.5, respectively. In order to calibrate and validate the AquaCrop model, version 1.6, intensive field investigation was done in a paddy plot at Sawah Sempadan compartment of the TAKRIS during the main and off-seasons of 2017. Data related to developmental stages of plants and yield was measured; historical data were collected from secondary sources. Water balance components were analyzed from the field observations of a paddy field. Irrigation water accounted for 59.6% of the total water input (irrigation and rainfall) during the off season and 76.2% of the total water input during the main season. Rainfall contributed 40.4% and 23.8% of total water input in the corresponding seasons. The grain yield of rice was 5.5 t/ha for the off-season and 5.9 t/ha for the main season. The model was validated with performance indicators of normalized root mean square error (2< NRMSE <4), prediction error (0.75<Pe<3), mean absolute error (120<MAE<160), and index of agreement (0.5<d<0.8). Satisfactory simulation results were obtained for biomass, (grain) yield and productivity. The average yield is projected to increase by 7.7%, 10.2% and 17.3% from baseline period in the off-season, and 8.6%, 11.5% and 18.4% in the main season under RCP4.5, RCP6.0 and RCP8.5, respectively. Simulation results also reveal that poor weed control measures and water stress conditions will reduce rice yields in the future. Under worst weed control, grain yield is expected to drop by 67% compared to weed-free condition. Simulation results suggest that crop evapotranspiration (ETc) is likely to decrease under all climate scenarios during both seasons, the maximum decrease being up to 10% under RCP8.5. Annual effective rainfall is predicted to increase marginally. Therefore, irrigation water requirement is projected to decrease by 3.5% in offseason and 5.5% in main season. Water productivity for continuous flooding shows an increasing trend in both off and main seasons, with the most significant increase under RCP8.5. Water productivity, based on irrigation plus effective rainfall (WPIrr+ER), is predicted to increase by 18%, 20% and 21% in off-season and 16%, 18% and 21% in main season under RCP4.5, RCP6.0 and RCP8.5 scenarios, respectively. Water productivity, based on crop evapotranspiration (WPETc), is predicted to increase by 22%, 23% and 26% in off-season, and 18%, 19% and 22% in main season under RCP4.5, RCP6.0 and RCP8.5 scenarios, respectively. Thus, AquaCrop simulation revealed a rising trend of potential rice yields and irrigation needs in conjunction with a CO2 fertilization. Suppressing stress on yield under rising temperature has been compensated by the ensuing increased CO2 fertilization. Moreover, proper weed control and water management practices have augmented yield under changing climate. This study would provide intuitive knowledge for Tanjung Karang Rice Irrigation Scheme for the development of sustainable productive rice yield under different management and environmental conditions.